Application d’une méthode d’étude quantitative et qualitative des rejets liquides hospitaliers au niveau de la Région de Marrakech Tensift El Haouz, Maroc - Asmaa, Qadouri; Latifa, Mouhir; Said, Belkadi Mohammed (European Scientific Journal, ESJ, 2016)
This study led to the development of a decision support tool to quantify the hospital effluent generated by public and private health care establishments in the region of Marrakech-Tensift-El Haouz situated in Morocco. The estimation concerns the consumption in drinking water, the production in wastewater and on the most consummate products collectively in the whole of the establishments of care and which join the sewer system (cleaner, soap, washing, Glutaraldehyde) based on the capacity litter, the hospitable vocations and the production rate. By having the results of quantification of the deposit rejected in the municipal network, the present study estimates then for the case of the city of Marrakesh the part of contribution of the hospital effluent in the municipal pollution.